Culturally Responsive Teaching and Ethnopedagogy Approach to Improve Local History Learning Studies in High School - Hafida, Mellina Nur (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Local history learning in Senior High School (SMA) in the Merdeka curriculum is given the freedom to present material. The content of the material is adjusted to the needs and local history of the community. This opportunity does not seem to be something that is often applied by educators. Culturally responsive teaching (CRT) and ethnopedagogy approaches offer solutions to increase relevance and effectiveness in learning local history. This research aims to develop strategies in the use of local wisdom through CRT and ethnopedagogical approaches to enrich the study in learning local history in high school. The method used in this study is in the form of a conceptual method, involving a literature review and theoretical analysis of elements in CRT and ethnopedagogy. The analysis was focused on the best way to integrate local wisdom into the history curriculum. Thus, a more meaningful learning experience can be created for students. The results of this study show that these two approaches are relevant when used as an approach in history learning. The CRT and ethnopedagogical approach allows students to relate historical material to their cultural identity, increasing understanding and appreciation of local history. The implementation of this strategy also increases students' critical awareness of relevant social and historical issues in their society. This research offers a flow of local history learning strategies with CRT and ethnopedagogy approaches